SUPERSTITIOUS BEHAVIOR AMONG JUDO, TAEKWONDO AND BOXING PLAYERS - Dureja Gaurav; Singh Gagandeep (Physical Education of Students)
Purpose: The present study was designed to measure superstitious behavior among Judo, Taekwondo and Boxing players. Material: Thirty (N=30) male inter-college level players with the age group of 19-25 years were selected through purposive sampling technique to act as subjects from affiliated colleges of Panjab University, Chandigarh. They were further divided into three groups: Group-A [Judo (n=10)], Group-B [Taekwondo (n=10)] and Group-C [Boxing (n=10)]. One Way Analysis of Variance (ANOVA) was applied to find out the differences among judo, taekwondo and boxing players. Where F values found significant, Least Significant Differences (LSD) Post-hoc test was applied to find out the direction and degree of difference. Results: The level of significance was set at 0.05. The result revealed significant differences among judo, taekwondo and boxing players on the sub parameters: clothing and appearance, preparation, team ritual and coach. However, no significant differences have been observed on the sub-parameters fetish, game/competition, prayer and parameter superstitious (Total). Conclusions: The obtained results showed significant differences on the sub-parameter Coach among Judo, Taekwondo and Boxing players. While calculating the mean values of entire groups, it has been observed that Boxing players demonstrate significantly better on the sub-parameter Coach. Therefore, it can be ascertained that Boxing players are more confident that coach bring a lucky charm to our game.